0120 SUVN-G3031, a Novel, Potent and Selective Histamine H3 Receptor Inverse Agonist for the Treatment of Narcolepsy: Preclinical Characterization. (12th April 2019) - Bhayrapuneni, Gopinadh; Kamuju, Venkatesh; Gandipudi, Sudhakar; Jayarajan, Pradeep; Abraham, Renny; Bojja, Kumar; Pandey, Santosh Kumar; Mekala, Venkat Reddy; Nirogi, Ramakrishna
Abstract: Introduction: Narcolepsy is a rare long-term brain disorder that causes a person to suddenly fall asleep at inappropriate times. H3R antagonists/ inverse agonists increase histaminergic neurotransmission and offer a therapeutic option for the treatment of narcolepsy. SUVN-G3031 is a potent H3R inverse agonist in the clinical development for the treatment of narcolepsy with or without cataplexy. Methods: SUVN-G3031 in-vitro binding, functional activity and phospholipidosis inducing liability was evaluated. Pharmacokinetic properties were evaluated after oral administration in mice, rat and dog. SUVN-G3031 was evaluated in brain microdialysis for neurotransmitter modulation in rats. In vivo functionality was assessed using R-α-methylhistamine induced dipsogenia assay. Tele - methylhistamine modulation was evaluated as a possible clinical biomarker. Long term toxicity studies up to 6 months in rats and 9 months in dogs have been completed along with genotoxicity and fetal development toxicity studies in rats and rabbits. Results: SUVN-G3031 exhibited no inter-species difference in binding affinity at H3R and displayed inverse agonism in functional GTPγS assay with >100 fold selectivity. SUVN-G3031 has no phospholipidosis inducing liability. SUVN-G3031 exhibited excellent pharmacokinetic properties and brain penetration. A single oral administration of SUVN-G3031 produced significant increase in acetylcholine, histamine, dopamine and norepinephrine levels in the cortex. SUVN-G3031 did not alter dopamine levels of striatum and nucleus accumbens indicating that it may not have addiction liability. SUVN-G3031 blocked R-α-methylhistamine induced water intake and produced dose-dependent increase in tele -methylhistamine levels in rat and mice brain and cerebrospinal fluid. Preclinical safety evaluation warrants its clinical development. Conclusion: SUVN-G3031 is an inverse agonist at H3R and results from the preclinical studies provide a strong evidence for the potential utility of SUVN-G3031 in treatment of narcolepsy and other sleep related disorders. Support (If Any): None